Catalytic cracking of polystyrene pyrolysis oil: Effect of Nb2O5 and NiO/Nb2O5 catalyst on the liquid product composition. (15th March 2022) - Amjad, Um-e-Salma; Tajjamal, Arshia; Ul-Hamid, Anwar; Faisal, Abrar; Zaidi, Syed Ammar Hussain; Sherin, Lubna; Mir, Amna; Mustafa, Maria; Ahmad, Nabeel; Hussain, Murid; Park, Young-Kwon
Graphical abstract: Research highlights: Thermal and catalytic pyrolysis of Polystyrene. Catalytic cracking of pyrolysis oil obtained from thermal pyrolysis. Nb2 O5 catalyst active towards cracking of dimers. NiO/Nb2 O5 catalyst active towards cracking of monomers. Lewis sites active towards cracking of dimers. Abstract: The catalytic cracking of polystyrene pyrolysis oil was investigated over a Nb2 O5 and a NiO/Nb2 O5 catalyst in a fixed bed reactor. First, the pyrolysis of two different polystyrene feedstock (polystyrene foam and polystyrene pellet) was carried out in a semi-batch reactor, and the resulting polystyrene pellets pyrolysis oil was selected for catalytic cracking reaction because of its high liquid yield (85%). Catalytic cracking experiments were then performed at different temperatures (350–500 °C) using Nb2 O5 or NiO/Nb2 O5 catalyst. Gas chromatography–mass spectrometry analysis of liquid product obtained from the catalytic cracking process showed that the dimers in the pyrolysis oil were converted to monomers during the catalytic cracking process. The catalytic cracking results also showed that the NiO/Nb2 O5 catalyst (having slightly higher acidic sites) had slightly higher activity for monomer conversion than the Nb2 O5 catalyst (having less acidic sites). X-ray diffraction, transmission electron microscopy, pyridine Fourier transform infrared spectroscopy, NH3 Temperature Programmed Desorption and X-ray photoelectron spectroscopy were used to characterize the catalyst. The highest catalytic cracking activity was observed at 400 °C with the Nb2 O5 catalyst with 4% toluene, 6% ethylbenzene, approximately 50% styrene, 13% α-methyl styrene, and only 6% of dimers in the liquid oil. The increase in temperature positively affected the yield of gases during catalytic cracking process.